Substrate-controlled ichnofacies along a marine sequence boundary: The Intra-Valanginian Discontinuity in central Neuquén Basin (Argentina) - Schwarz, Ernesto (2012)
The Intra-Valanginian Discontinuity in the Neuquén Basin (Argentina) marks a dramatic sea-level fall within Lower Cretaceous strata, and can be mapped for tens of kilometers both along depositional strike and dip. In the proximal region of the lowstand configuration, the subaerial segment of the sequence boundary is demarcated by alluvial conglomerates (basal Mulichinco Formation) onto deep-marine black shales (Vaca Muerta Formation). In the distal marine realm, the time-equivalent marine sequence boundary separates black shales and marls beneath from shallow-marine carbonate deposits above. This paper documents and discusses substrate-controlled trace fossils demarcating the marine sequence boundary across more than 30. km in a proximal-distal transect in order to shed light onto processes affecting the sea-floor during the generation, biogenic modification, and preservation of this regionally extensive omission surface.The downdip expression of the marine sequence boundary is well-exposed across a 20-km long, strike-oriented outcrop. Everywhere in this region the discontinuity is demarcated by robust Thalassinoides with well-defined walls and circular cross-sections, suggesting that the marly substrate was relatively firm during excavation. The burrow system is filled with bioclasts of echinoids and bivalves not present in underlying strata, up to pebble-size intraclasts that were eroded from the underlying succession, and authigenic minerals (glauconite, phosphates). This trace-fossil suite illustrates the Glossifungites Ichnofacies. The updip expression of the marine sequence boundary in the study area was recorded in a cored well located about 20. km from the outcrops. As in the distal region, a first generation of passively filled Thalassinoides excavated into a firm marly substrate is attributed to the Glossifungites Ichnofacies. However, this suite is cross-cut at the top by Gastrochaenolites and other unidentified borings. Bored intraclasts also occur above the omission surface. This trace-fossil suite represents the Trypanites Ichnofacies.The Intra-Valanginian Discontinuity records a complex history after the onset of the dramatic sea-level fall. Extensive erosion and exhumation of previous sediments, as well as early cementation, combined to produce different types of substrates during the generation of the omission surface (firmgrounds and hardgrounds). Colonization of firm substrates probably started firstly in proximal regions, when relative sea-level was still falling. During early transgression, firmgrounds were occupied in distal regions and borers colonized the hardgrounds developed in proximal regions. Thus, the surface demarcates a composite surface, involving a sequence boundary plus a transgressive surface, draped in turn by a mixing of sediments suggesting siliciclastic starvation. The generation and preservation of the features associated with the Intra-Valanginian Discontinuity are thought to result from the combination of a ramp-type pre-existing morphology, coupled with a high-amplitude sea-level fall and a relatively deep-marine setting prior to the formation of the omission surface. © 2012 Elsevier B.V.